PELATIHAN PENGGUNAAN APLIKASI LABORATORIUM BANK BERBASIS WEB UNTUK GURU GURU MGMP AKUNTANSI DAN PERBANKAN - Sistiyarini, Evi; Rokhmania, Nur’aini; Kristijadi, Emanuel (Jurnal AbdiMas Nusa Mandiri, 2026)
This community service program activity is a collaboration between Hayam Wuruk Perbanas University and the Surabaya City Accounting and Banking MGMP. There are three schools in Surabaya that have a Banking major but do not yet have a web-based banking laboratory application that is used to support banking transactions for students. The application used by schools that have a banking major is a conventional banking laboratory application based on LAN (Local Area Network) which can only be accessed in the laboratory room, while schools that have a sharia banking major do not yet have a sharia banking laboratory application. The stages of this activity include the preparation stage, application development stage, implementation of training and evaluation of activities. This activity aims to share information with teachers on the use of web-based banking laboratory applications for banking transactions. The methods used were training and mentoring. The result of this activity is the creation of web-based conventional and Islamic banking laboratory applications that can be used by teachers of the Surabaya City Accounting and Banking MGMP. Based on the training results, vocational high school teachers and students are able to use the web-based banking laboratory application for banking transactions, so that the learning process is not only carried out manually, but also digitally.